An automatic classification of urban texture: form and compactness of morphological homogeneous structures in Barcelona - Nicola Colaninno; Josep Roca; Karin Pfeffer (European Regional Science Association (ERSA), 2011)
Cities can be classified according to morphology of their urban structures. Depending on the spatial relations between built-up and empty spaces, blocks and streets (or squares) we can distinguish compact or fragmented cities as well as continuous or discontinuous. The configuration of the physical elements, with their own functional dynamics, produces different "drawings" in the cities. By disaggregating the urban fabric into different components, it is possible to study the topological, geometrical and dimensional relationships between the elements. This paper investigates the morphology of the city of Barcelona; the main objective is to identify and automatically classify morphological homogeneous categories and determine the level of compactness of urban textures. The classification consists of several steps. A first analysis was performed to identify different typologies in the built-up area and typify urban patterns by using geometrical and relational characteristics, such as shape of buildings and spatial interaction between them in terms of distance. This was followed by an automatic classification of urban fabrics with a homogeneous character. Finally, the morphological compactness was determined, calculated as "equilibrium" between size and distances of buildings. In order to make automatic classification of urban textures, we calibrated a set of indicators, capable to describe specific formal and functional characters and, by using GIS and statistical analysis such as factor and cluster analysis, we categorized several homogeneous "morphological neighbourhoods". This classification process is based on geometric characteristics, assuming that, in general, different functions require different forms. By aggregating subjects of similar behaviour we could identify to which kind of urban configuration a neighbourhood possibly belongs. The outcome of this study can support urban planning and management in identifying target areas concerning socio-economic interventions within urbanized territories.
Keywords: 330